Three-dimensionally macroporous, Si and N-incorporated graphene aerogels for gas adsorbents - Yun, Sol; Kim, Hyungdae; Lee, Hyunjoo; Park, Ho Seok (AMER SCIENTIFIC PUBLISHERS, 2015)
Three-dimensionally macroporous, Si and N-incorporated graphene aerogels (3D SN-rGOAs) are successfully fabricated through a self-assembly, vapor deposition of (3-aminopropyl)triethoxysilane (APTES), and thermal treatment for gas adsorption applications. As investigated by spectroscopic methods, the interaction between oxygen-containing groups of GO and APTES results in the uniform incorporation of Si and N atoms on the surface of 3D SN-rGOAs. The resulting SN-rGOAs are composed of the 3D interconnected macroporous structures with the mesoporosity by means of the reorganization of rGO sheets. The existence and distribution of Si and N atoms are characterized and their atomic compositions are 6.19 and 4.24%, respectively. Even after the incorporation of Si and N atoms, the surface area and pore volume of SN-rGOAs are slightly larger than those of pristine rGOAs due to thermal treatment at 900 degrees C, which also promotes the further restoration of sp(2) conjugation. The as-obtained SN-rGOAs show a dramatic improvement in the adsorption capacities and kinetics of CO2 and SO2 because of the existences of Si and N atoms and 3D macroporous continuity.
Keywords: HIGH-PERFORMANCE; CARBON NANOTUBES; ENERGY-STORAGE; SUPERCAPACITORS; ARCHITECTURES; CONVERSION; FRAMEWORKS; CAPTURE